Development of Student Entrepreneurship Skills in LKP Kresna Informatika - Usup Usup; Supriyono Supriyono; Hardika Hardika; Endang Sri Redjeki (STAI Miftahul Ula Nganjuk, 2020)
The purpose of this study is 1) Describe the ideal and feasible model of the allocation of an entrepreneurship education curriculum for learners at a course institution. 2) Describe an ideal and feasible model of an entrepreneurship education learning strategy for learners in a course institution. Qualitative research is also called naturalistic research. Subjects in this study are students and alumi in course programs organized by LKP Kresna Informatika such as English courses courses, computer and office accounting. Data collection techniques in the context of this study have a significant role considering the quality of various types of data obtained at each stage of module development. Observation and documentation, interviews and tests are the data collection techniques used in this research before it will be analyzed. Stages of data analysis pursued after the need for data both secondary and primary when it has been fulfilled which includes; (1) data reduction, (2) display data, and (3) conclusion drawing/verification. The results in the study conclude that to establish entrepreneurial attitude in the courses and training programs conducted by LKP Kresna Informatika include; 1) The prerequisite of one's attitude input and one's entrepreneurial nature in LKP Kresna Informatika includes; discipline, high commitment, honest, reative and Innovative. 2) Design learning strategies in growing and developing entrepreneurship skills of learners in LKP Kresna Informatika through a special approach that is called 4 in 1 or with four stages. 3) Implementation of learning strategies in growing and developing entrepreneurship skills of learners in LKP Kresna Informatika; Identification of Business Opportunities, entrepreneurship learning based on the development of attitudes, knowledge and entrepreneurship skills, Evaluation of Learning Outcomes and Business Assistance and Pioneering.